Binomialized !!

Algebra Level pending

If ( 1 + b x ) n = 1 + a 1 x 1 + a 2 x 2 + a 3 x 3 + a 4 x 4 + . . . + ( b x ) n { (1+bx) }^{ n }=1+{ a }_{ 1 }{ x }^{ 1 }+{ a }_{ 2 }{ x }^{ 2 }+{ a }_{ 3 }{ x }^{ 3 }+{ a }_{ 4 }{ x }^{ 4 }+...+(bx)^{ n } , where n n is a positive integer , a 1 = 12 , a 4 = 4 a 2 { a }_{ 1 }=12 , { a }_{ 4 }=4{ a }_{ 2 } . Calculate n + b n+b


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Ahmad Hesham
Aug 2, 2014

We are given ( 1 + b x ) n { (1+bx) }^{ n } in this form : ( 1 + b x ) n = 1 + a 1 x 1 + a 2 x 2 + a 3 x 3 + a 4 x 4 + . . . + ( b x ) n ( 1 ) { (1+bx) }^{ n }=1+{ a }_{ 1 }{ x }^{ 1 }+{ a }_{ 2 }{ x }^{ 2 }+{ a }_{ 3 }{ x }^{ 3 }+{ a }_{ 4 }{ x }^{ 4 }+...+(bx)^{ n }\quad \rightarrow \quad (1)

but we can get another form by using the b i n o m i a l binomial t h e o r e m theorem : ( 1 + b x ) n = 1 + n C 1 ( b x ) 1 + n C 2 ( b x ) 2 + n C 3 ( b x ) 3 + n C 4 ( b x ) 4 + . . . + ( b x ) n ( 2 ) { (1+bx) }^{ n }=1+{ _{ n }{ C }_{ 1 } }(b{ x) }^{ 1 }+{ _{ n }{ C }_{ 2 } }(b{ x) }^{ 2 }+{ _{ n }{ C }_{ 3 } }({ bx) }^{ 3 }+{ _{ n }{ C }_{ 4 } }(b{ x) }^{ 4 }+...+(bx)^{ n }\quad \rightarrow \quad (2) {As "C" refers to the Combination}

From (1),(2) : 1 + a 1 x 1 + a 2 x 2 + a 3 x 3 + a 4 x 4 + . . . + ( b x ) n = 1 + n C 1 ( b x ) 1 + n C 2 ( b x ) 2 + n C 3 ( b x ) 3 + n C 4 ( b x ) 4 + . . . + ( b x ) n 1+{ a }_{ 1 }{ x }^{ 1 }+{ a }_{ 2 }{ x }^{ 2 }+{ a }_{ 3 }{ x }^{ 3 }+{ a }_{ 4 }{ x }^{ 4 }+...+(bx)^{ n }=1+{ _{ n }{ C }_{ 1 } }(b{ x) }^{ 1 }+{ _{ n }{ C }_{ 2 } }(b{ x) }^{ 2 }+{ _{ n }{ C }_{ 3 } }({ bx) }^{ 3 }+{ _{ n }{ C }_{ 4 } }(b{ x) }^{ 4 }+...+(bx)^{ n }

By equalizing the binomial coefficients : a 1 = n C 1 ( b ) , a 2 = n C 2 ( b ) 2 , a 3 = n C 3 ( b ) 3 , a 4 = n C 4 ( b ) 4 { a }_{ 1 }={ _{ n }{ C }_{ 1 } }(b)\quad ,\quad { a }_{ 2 }={ _{ n }{ C }_{ 2 } }{ (b) }^{ 2 }\quad ,\quad { a }_{ 3 }={ _{ n }{ C }_{ 3 } }{ (b) }^{ 3 }\quad ,\quad { a }_{ 4 }={ _{ n }{ C }_{ 4 } }{ (b) }^{ 4 } a 1 = n b = 12 ( 3 ) \boxed { \therefore { a }_{ 1 }=nb=12 } \longmapsto \quad (3) Now this one is i m p o r t a n t important , but we'll keep it for now

Well , things got a little bit stuffed right here , so lets clean it up using the information we didn't use yet !

a 4 = 4 a 2 4 n C 2 ( b ) 2 = n C 4 ( b ) 4 \because { a }_{ 4 }=4{ a }_{ 2 }\\ \therefore 4{ _{ n }{ C }_{ 2 } }{ (b) }^{ 2 }={ _{ n }{ C }_{ 4 } }{ (b) }^{ 4 }

4 ( b ) 2 ( b ) 4 = n C 4 n C 2 4 ( b ) 2 = n C 4 n C 3 × n C 3 n C 2 4 ( b ) 2 = n 4 + 1 4 × n 3 + 1 3 4 ( b ) 2 = ( n 3 ) ( n 2 ) 12 \\ \frac { 4{ (b) }^{ 2 } }{ { (b) }^{ 4 } } =\frac { _{ n }{ C }_{ 4 } }{ _{ n }{ C }_{ 2 } } \\ \\ \frac { 4 }{ { (b) }^{ 2 } } =\frac { _{ n }{ C }_{ 4 } }{ _{ n }{ C }_{ 3 } } \times \frac { _{ n }{ C }_{ 3 } }{ _{ n }{ C }_{ 2 } } \\ \\ \frac { 4 }{ { (b) }^{ 2 } } =\frac { n-4+1 }{ 4 } \times \frac { n-3+1 }{ 3 } \\ \\ \frac { 4 }{ { (b) }^{ 2 } } =\frac { (n-3)(n-2) }{ 12 } \\ \\

Now , using (3) , we'll substitute b b by 12 n \frac { 12 }{ n } :

4 ( 12 n ) 2 = n 2 5 n + 6 12 n 2 3 = n 2 5 n + 6 \frac { 4 }{ { (\frac { 12 }{ n } ) }^{ 2 } } =\frac { { n }^{ 2 }-5n+6 }{ 12 } \\ \\ \frac { { n }^{ 2 } }{ 3 } ={ n }^{ 2 }-5n+6

After simplifying it should be like this : 2 n 2 15 n + 18 = 0 2{ n }^{ 2 }-15n+18=0 , ( 2 n 3 ) ( n 6 ) = 0 (2n-3)(n-6)=0 n = 3 2 O r 6 \therefore \quad n=\cfrac { 3 }{ 2 } \quad Or\quad 6 & of course the solution n = 3 2 n=\cfrac { 3 }{ 2 } is rejected as n is a positive integer

From (3) we'll find out that b = 2 b=2

n + b = 8 \boxed { \therefore n+b=8 }

If anybody has a better solution , please post it !!

Ahmad Hesham - 6 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...